Perceived Ease of Use and Price Fairness on Customer Loyalty Among Shopee Users: The Role of Brand Love as a Mediating Variable - Nurseha Nurseha; Mulyati Mulyati; Desi Rubiyanti (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the direct and indirect effects of perceived ease of use and price fairness on customer loyalty, using brand love as a mediating variable among Shopee users. Research Method: A quantitative descriptive approach was employed. Data were collected from 72 active Shopee users in Dompu Regency via purposive sampling using a 5-point Likert-scale questionnaire and analyzed using PLS-SEM in SmartPLS. Results and Discussion: Perceived ease of use directly enhances customer loyalty but fails to foster brand love. Conversely, price fairness significantly builds brand love without directly impacting customer loyalty. Furthermore, brand love fully mediates the relationship between price fairness and customer loyalty, but does not mediate the relationship between price fairness and perceived ease of use. Implications: E-commerce platforms must prioritize transparent and fair pricing to build emotional connections, as operational ease is merely a standard requirement. Future studies should expand the sample size and geographic scope, and incorporate variables such as live streaming and e-WOM. Originality: This study extends the Theory of Reasoned Action by demonstrating that rational price evaluations alone do not secure permanent behavioral loyalty; affective transformation (brand love) is required.